Hypnocaring as a Support Model for Reducing Stress Levels in People Living With HIV/AIDS (PLHIV) - Permatasari, Dian; Pratiwi, Iva Gamar Dian; Mulyadi, Eko; Puspitasari, Dian Ika (Journal of Applied Nursing and Health, 2023)
Background: People Living With HIV/AIDS (PLHIV) are a group that experiences significant psychological stress, including higher levels of stress than the general population. This research aims to determine the effectiveness of hypnotherapy in reducing stress in PLHIV patients and whether this method can be an effective alternative in reducing stress and improving the quality of life in PLHIV patients in Sumenep Regency. Hypnotherapy is a form of alternative therapy that involves suggestion and visualization to influence the subconscious mind. Methods: This research method uses a quasi-experiment with a research design involving two groups containing 30 research samples (Two groups Pre-Post Test), where the variables are PLWHA aged 21-50 years, with a side method using purposive sampling. The research instrument used the DASS (Depression Anxiety Stress Scale) questionnaire. Results: There were significant differences Between groups in Experiments and groups control where the value was 0.009 < 0.05. There is a significant difference between Pretest and Posttest in the Experimental group with an alpha value of 0.000 < 0.05; the level of influence of Hypnotherapy was 62.8%, and the other 37.2% were influenced by factors other than outside therapy. Conclusion: Based on the three results of the calculation tests above, it can be concluded that hypnotherapy is effective in reducing stress in HIV/AIDS patients (PLWHA) in Sumenep Regency